Hydrogeological investigation of landslides Urbas and Čikla above the settlement of Koroška Bela - Mitja, Janža; Luka, Serianz; Dejan, Šram; Matjaž, Klasinc (Geologija, 2018)
The area above the settlement of Koroška Bela is highly prone to slope mass movements and poses a high risk for the safety of the settlement. To get an insight into the hydrogeological conditions and processes which can affect mass movements in this area, hydrogeological investigations, including hydrogeological mapping, discharge measurements of springs, performance of infiltrometer and slug tests were performed. The results of these investigations show complex and heterogeneous hydrogeological conditions, predisposed by geological and tectonic setting and active mass movements which cannot be uniformly described. Observed large fluctuations in the rate of discharge of springs and groundwater level in observation wells are highly dependent on meteorological conditions. Estimated hydraulic conductivity of the soil is relatively high (2×10-4 m/s) and reflects the loose structure and high content of organic matter in the upper part of the forest soil. Hydraulic conductivity of more permeable sections of boreholes is in general higher in the upper parts, in predominantly gravel layers (in range from 2×10-3 to 1×10-5 m/s), than in the deeper clayey gravel parts (3×10-5 to 1×10-7 m/s). In the area of the Čikla landslide the average hydraulic conductivity is estimated at 8.99×10-4 m/s and is higher than in the area of the Urbas landslide (3.05×10-4 m/s).